2011
DOI: 10.1037/a0023769
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' implicit theories predict desire for vengeance after peer conflicts: Correlational and experimental evidence.

Abstract: Why do some adolescents respond to interpersonal conflicts vengefully, whereas others seek more positive solutions? Three studies investigated the role of implicit theories of personality in predicting violent or vengeful responses to peer conflicts among adolescents in Grades 9 and 10. They showed that a greater belief that traits are fixed (an entity theory) predicted a stronger desire for revenge after a variety of recalled peer conflicts (Study 1) and after a hypothetical conflict that specifically involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 87 publications
(147 reference statements)
10
156
0
Order By: Relevance
“…However, research that focuses just on mindset or just on academic achievement could be synthesized to prove our conclusion, especially in studies involving the same variables. For example, Yeager, Trzesniewski, Tirri, Nokelainen, and Dweck (2011) discussed the negative role in attribution of a fixed mindset and the positive role of intervention in emotion with a growth mindset. Moreover, some of the studies reviewed (e.g., Cury et al, 2008;Zeng et al, 2016;Mouratidis et al, 2017) indicated that attributions and emotions were important mediators between mindset and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…However, research that focuses just on mindset or just on academic achievement could be synthesized to prove our conclusion, especially in studies involving the same variables. For example, Yeager, Trzesniewski, Tirri, Nokelainen, and Dweck (2011) discussed the negative role in attribution of a fixed mindset and the positive role of intervention in emotion with a growth mindset. Moreover, some of the studies reviewed (e.g., Cury et al, 2008;Zeng et al, 2016;Mouratidis et al, 2017) indicated that attributions and emotions were important mediators between mindset and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, mindsets are quite stable, yet they are alterable through educational interventions (Aronson, Fried, & Good, 2002;Blackwell, Trzesniewski, & Dweck, 2007;Dweck, 2012;Yeager, Trzesniewski, Tirri, Nokelainen, & Dweck, 2011;. The main feature of such interventions has been to teach students about the neuroplasticity of the brain and its potential to change and reorganize when people learn and practice new ways of thinking (Aronson, Fried, & Good, 2002;Blackwell, Trzesniewski, & Dweck, 2007;.…”
Section: Educational Interventions On Mindsetsmentioning
confidence: 99%
“…In that experiment the participants read a scientific article describing either that intelligence was malleable and able to change (growth mindset condition) or fixed and immutable (fixed mindset condition), a manipulation that has proven to induce mindsets (Yeager, Trzesniewski, Tirri, Nokelainen, & Dweck, 2011) before they completed the same task as Moser et al (2011). The study evaluated how the induction influenced both stimulus-locked and response-locked functions as well as indices of behavioral adjustment following errors, such as PES (Rabbitt, 1966), PEA (Laming, 1979) and post-error reduction of interference (PERI; Ridderinkhof, 2002).…”
Section: Brain Research On Students' Mindsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a more positive note, our results suggest that intervening in the 'revenge stream' may be an effective way to prevent crime and violence from escalating. Given how strongly RMD is related to attitudes favourable to revenge, changing such attitudes through cognitive-educational programming might prove to be helpful in efforts to reduce youth violence (Yeager et al, 2011(Yeager et al, : 1101.…”
Section: Policy Implicationsmentioning
confidence: 99%